Kontribusi Pendekatan Filsafat dalam Studi Islam dan Studi Qur’an - Ahmad Afifi; Saifuddin Yuliar (ISME : Journal of Islamic Studies and Multidisciplinary Research, 2025)
Recent developments in Islamic studies have begun to show signs that Islam is no longer understood solely in historical and doctrinal terms, but has become a complex phenomenon. In its evolution, various approaches have emerged to examine different dimensions of Islamic teachings. One approach that can be employed to understand religious teachings is the philosophical approach. This paper aims to describe the contribution of the philosophical approach to Islamic studies, including its application in Qur’anic studies. Using a qualitative method of library research, this paper finds that, first, the philosophical approach in religious studies emphasizes a philosophical framework in investigating religious teachings. Philosophy continually raises questions that help maintain the relevance of religion, such as those concerning the existence of God, the nature of the human self and soul, as well as the purpose and ultimate end of human life. The philosophical approach in religious studies positions religion as an object of rational inquiry using philosophical tools, rather than as a branch of theology. It is characterized by being logical, metaphysical, comprehensive-ontological, epistemological, and ethical. Second, the presence of rational elements in philosophy makes a significant contribution to the development of the Islamic scholarly tradition. This approach has encouraged the formation of disciplines such as ‘ilm al-kalām (Islamic theology), fiqh (Islamic jurisprudence), and tafsīr (Qur’anic exegesis). Third, this approach opens space for hermeneutical methods, which now play a crucial role in contemporary Qur’anic studies.